Elimination of Management Bias from Production Functions Fitted to Cross-Section Data: A Model and an Application to African Agriculture - Massell, Benton F. (Econometrica, 1967)
Benton F. Massell, Elimination of Management Bias from Production Functions Fitted to Cross-Section Data: A Model and an Application to African Agriculture, Econometrica, Vol. 35, No. 3/4 (Jul. - Oct., 1967), pp. 495-508